Semiconductor device
Patent Information
- Application Number
- JP2022099050
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-20
- Publication Date
- 2025-04-09
AI Technical Summary
【0021】 本発明によれば、PPSケースと封止材の間の剥離を抑制し、信頼性の高い半導体装置を提供することができる。
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a semiconductor device, and more particularly to a highly reliable semiconductor device that is prevented from stress concentration and moisture intrusion. [Background technology]
[0002] Power semiconductor modules are widely used in fields that require efficient power conversion. For example, their application is expanding to the power electronics field, such as industrial equipment, electric vehicles, and home appliances. These power semiconductor modules contain switching elements and diodes, and the elements use Si (silicon) semiconductors and SiC (silicon carbide) semiconductors.
[0003] A power semiconductor module is manufactured by encapsulating a chip made of a semiconductor element and conductive connection members such as a lead frame connected to the chip with an insulating resin encapsulant. The resin encapsulant contains a thermosetting resin and an inorganic filler as main components.
[0004] As an example of a power semiconductor module, a semiconductor device is known in which a semiconductor element mounted on a laminated substrate and a conductive connecting member are sealed with a thermosetting resin filled in a case (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-150466 A Summary of the Invention [Problem to be solved by the invention]
[0006] In semiconductor devices, cases filled with thermosetting resin are generally composed of thermoplastic resin such as polyphenylene sulfide (PPS) or polybutylene terephthalate (PBT) and inorganic filler. Among these, cases containing PPS as a material (hereinafter referred to as PPS cases) have a problem of peeling between the PPS case and a sealing material containing a thermosetting resin such as epoxy resin. [Means for solving the problem]
[0007] When peeling occurs between the thermosetting resin and the PPS case, the peeled portion can become a path for the intrusion of substances that impair the properties of the components inside the semiconductor device, such as moisture and corrosive gases, into the semiconductor device. In particular, when partial peeling occurs between the encapsulant and the PPS case, problems can arise in that stress is concentrated at the location where the encapsulant and the PPS case maintain contact without peeling.
[0008] As a result of extensive research, the inventors discovered that it is possible to prevent a decrease in reliability by designing the contact surface of the PPS case with the sealing material in a structure that can suppress peeling from the sealing material, and thus completed the present invention.
[0009] That is, according to one embodiment, the present invention provides a semiconductor device, A case including an inorganic filler in a matrix including polyphenylene sulfide; A semiconductor element mounted on a laminated substrate; An encapsulant for encapsulating the semiconductor element; A semiconductor device comprising: The present invention relates to a semiconductor device, wherein the inorganic filler is exposed from the matrix on the surface of the case facing the sealing material.
[0010] In the semiconductor device, it is preferable that the content of the inorganic filler with respect to the total mass of the case is 40 to 70 mass %, and the exposed area ratio of the inorganic filler is 10 to 60%.
[0011] In the semiconductor device, the inorganic filler is preferably a fibrous inorganic filler.
[0012] In the semiconductor device, the inorganic filler is preferably selected from a metal oxide or a metal nitride.
[0013] In the semiconductor device, it is preferable that the sealing material contains a thermosetting resin selected from the group consisting of epoxy resin, maleimide resin, cyanate resin, and oxazine resin.
[0014] In the semiconductor device, it is preferable that the surface of the case facing the sealing material is an etched surface.
[0015] In the semiconductor device, it is preferable that the exposed inorganic filler is in contact with the sealing material.
[0016] In the semiconductor device, it is preferable that a silane coupling agent layer is formed on a surface of the case facing the sealing material.
[0017] In the semiconductor device on which the silane coupling agent layer is formed, the silane coupling agent layer is preferably in contact with the sealing material.
[0018] According to another embodiment, the present invention provides a method for manufacturing a semiconductor device, comprising the steps of: A step of producing a case comprising an inorganic filler in a matrix comprising polyphenylene sulfide; immersing the case in an etching solution to expose the inorganic filler from the matrix; a step of placing a semiconductor element mounted on a laminated substrate in the case obtained by the exposing step; filling a sealing material into the case in which the semiconductor element is disposed, and sealing the case; The present invention relates to a method for manufacturing a semiconductor device,
[0019] The method for manufacturing a semiconductor device preferably further comprises, before the step of arranging the semiconductor element, a step of forming a silane coupling agent layer on the surface on which the inorganic filler is exposed.
[0020] In the method for manufacturing a semiconductor device, the silane coupling agent is preferably a silane coupling agent containing an epoxy group or an amino group. Effect of the Invention
[0021] According to the present invention, it is possible to provide a highly reliable semiconductor device that suppresses peeling between the PPS case and the sealing material. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a conceptual cross-sectional view showing a cross-sectional structure of a semiconductor device according to the present invention. [Diagram 2] FIG. 2 is a graph of a reference example, showing the relationship between the etching time (hr) and the exposed area ratio (%) of silica when a resin composite substrate of PPS and silica was etched by immersing it in concentrated nitric acid at 80° C. [Diagram 3] FIG. 3 is a graph according to an embodiment, showing the relationship between the silica exposed area ratio (%) of a resin composite substrate of PPS and silica and the adhesive strength (MPa) with an epoxy resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. However, the present invention is not limited to the embodiment described below.
[0024] According to one embodiment, the present invention relates to a semiconductor device, the semiconductor device comprising a case including an inorganic filler in a matrix including polyphenylene sulfide, a semiconductor element mounted on a laminated substrate, and an encapsulant that encapsulates the semiconductor element, the inorganic filler being exposed from the matrix including polyphenylene sulfide on a surface of the case facing the encapsulant.
[0025] 1 is a conceptual cross-sectional view of a power semiconductor module, which is an example of a semiconductor device according to this embodiment. The illustrated power semiconductor module has a laminated structure in which a semiconductor element 11 and a laminated substrate 12 are bonded onto a heat sink 13 by a bonding layer 17. A case 16 incorporating an external terminal 15 is attached to the heat sink 13. The electrodes of the semiconductor element 11 and the laminated substrate 12 are connected by a lead frame 18, which is a conductive connecting member. The semiconductor element 11 and the external terminal 15 are also connected by an aluminum wire 14. A sealant 20 is filled in the space defined by the case 16 and the heat sink 13, in contact with the semiconductor element 11, the laminated substrate 12, the lead frame 18, and the aluminum wire 14, which is a conductive connecting member.
[0026] The semiconductor element 11 is a power chip such as an IGBT (Insulated Gate Bipolar Transistor) or a diode chip, and may be a Si device or a wide-gap semiconductor device such as a SiC device, a GaN device, a diamond device, or a ZnO device. These devices may also be used in combination. For example, a hybrid module using a Si-IGBT and a SiC-SBD may be used. The number of semiconductor elements mounted may be one or more.
[0027] The laminated substrate 12 can be composed of an insulating substrate 122, a first conductive plate 121 formed on one of its main surfaces, and second conductive plates 123a, 123b formed on the other main surface. The insulating substrate 122 can be made of a material having excellent electrical insulation and thermal conductivity. Examples of the material for the insulating substrate 122 include Al2O3, AlN, and SiN. In particular, for high-voltage applications, a material having both electrical insulation and thermal conductivity is preferable, and AlN and SiN can be used, but are not limited to these. The first conductive plate 121 and the second conductive plates 123a, 123b can be made of metal materials such as Cu and Al, which are excellent in workability. The conductive plates may be Cu or Al that have been treated with Ni plating or the like for the purpose of rust prevention. Methods for disposing the conductive plates 121, 123a, 123b on the insulating substrate 122 include a direct copper bonding method and an active metal brazing method. In the illustrated embodiment, two second conductive plates 123a, 123b are discontinuously provided on an insulating substrate 122, with one second conductive plate 123a functioning as an electrode to be joined to the semiconductor element 11 and the other second conductive plate 123b functioning as an electrode to be connected to the lead frame 18.
[0028] The lead frame 18 is a conductive connection member that connects the semiconductor element 11 and the second conductive plate 123b and the like. Specifically, the lead frame 18 is joined to the electrode (front surface electrode 11a) of the semiconductor element 11 on the opposite side to the electrode (rear surface electrode) 11b that contacts the laminated substrate 12, by a bonding layer 17 such as a solder material. The lead frame 18 is also joined to the wiring parts of the second conductive plate 123b and the like by a bonding layer 17 such as a solder material. The lead frame 18 may be made of a metal such as copper or an alloy containing copper. A Ni or Ni alloy layer, or a Cr or Cr alloy layer may be formed on the surface of the lead frame 18 by plating or the like. In this case, the film thickness of the Ni or Ni alloy layer, or the Cr or Cr alloy layer may be about 20 μm or less. The lead frame may be connected to an extraction terminal (not shown).
[0029] The heat sink 13 is made of a metal such as copper or aluminum having excellent thermal conductivity. The heat sink 13 may be coated with Ni or a Ni alloy to prevent corrosion. The heat sink 13 may be a cooler having a function of water cooling or air cooling. There may also be a semiconductor device in which the case 16 is attached to the laminated substrate 12 and the heat sink 13 is not attached to the case 16.
[0030] The bonding layer 17 can be formed using lead-free solder. For example, Sn-Ag-Cu, Sn-Sb, Sn-Sb-Ag, Sn-Cu, Sn-Sb-Ag-Cu, Sn-Cu-Ni, Sn-Ag, etc. can be used, but are not limited to these. Alternatively, the bonding layer can be formed using a connecting material containing fine metal particles, such as a sintered body of nano-silver particles.
[0031] The case 16 is a molded body containing an inorganic filler in a matrix containing polyphenylene sulfide (PPS), and may generally be molded integrally with the metal external terminal 15. The matrix is a resin that surrounds particles of the inorganic filler, holds the particles, and forms a case, and may be an insulating resin. PPS is the main component of the matrix, and may be 50% by mass or more of the total mass of the matrix, and may also be 60% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more. In addition to PPS, an epoxy resin or a phenolic resin may be added to the matrix, for example, at about 10% by mass or less. In addition to the matrix and the inorganic filler, the case 16 may optionally contain a normal additive of about less than 5% by mass with respect to the total mass of the case, and the additive may include a flame retardant and a plasticizer.
[0032] The case 16 generally has a shape surrounding the side of the semiconductor element 11, the laminated substrate 12 bonded thereto, and conductive connection members such as lead frames and wires. The bottom of the case 16 is open and may be frame-shaped, and the bottom surface of the frame may be bonded to the heat sink 13 or the laminated substrate 12 via a bonding material. The outer surface of the case 16 constitutes a part of the outer surface of the semiconductor device. Here, the side of the semiconductor element 11 refers to a surface perpendicular to the front surface electrode 11a and the back surface electrode 11b. The inner surface of the case 16 includes a surface facing the sealing material 20. The surface facing the sealing material 20 refers to a surface that is in direct contact with the sealing material 20 or adjacent to the sealing material 20 via a surface treatment layer such as a silane coupling agent layer between the sealing material 20 and the case 16. In this specification, the surface of the case 16 that faces the sealing material 20 is also referred to as the sealing material facing surface F. In the case 16, the sealing material facing surface F may generally be the inner side surface of the case 16.
[0033] As described later, PPS does not easily form bonds with other organic or inorganic substances, and does not easily bond with thermosetting resins such as epoxy resins, and the adhesion between PPS and thermosetting resins (sealing materials) such as epoxy resins is not high. Therefore, when the inorganic filler is covered with PPS, peeling may occur between the case and the sealing material. On the other hand, since the inorganic filler and the thermosetting resin such as epoxy resin have high adhesion, it is preferable that the inorganic filler is exposed from the matrix containing PPS over the entire sealing material facing surface F. This is because if partial peeling occurs between the sealing material 20 and the case in the sealing material facing surface F, there is a concern that stress will be concentrated in the part that is not peeled off.
[0034] The PPS may be any PPS having a repeating unit represented by the following formula (1), and may consist of only this repeating unit. [ka] Therefore, it may be a linear PPS or a crosslinked PPS.
[0035] The case is preferably insulating, and therefore the inorganic filler may be a metal oxide or metal nitride, and may be selected from, for example, fused silica, silica (silicon oxide), alumina, aluminum hydroxide, titania, zirconia, aluminum nitride, talc, clay, mica, and glass fiber, but is not limited thereto. In particular, metal oxides such as silica and alumina having OH groups on the surface are preferred. For example, this is because the epoxy groups of the epoxy resin of the sealing material and the OH groups are easily bonded to each other, and therefore have adhesive strength. Two or more different inorganic fillers may also be used in combination.
[0036] The inorganic filler is preferably fibrous. Here, fibrous refers to a shape having an aspect ratio (length / diameter) of approximately 10 to 100, which can supplement the strength of the resin. The fibrous shape may also be called needle-like or rod-like. In addition, the inorganic filler may have an average particle diameter of approximately 10 μm to 100 μm. The average particle diameter of the fibrous inorganic filler refers to the average major axis. The average value may be a value obtained by a laser diffraction particle size distribution analyzer.
[0037] When the total mass of the materials constituting case 16 is taken as 100%, the content (filling rate) of the inorganic filler may be, for example, 40 to 70 mass%, or 45 to 60 mass%, with the remainder being the matrix. Pellets and compounds containing a matrix containing PPS and an inorganic filler as main components are commercially available, and a person skilled in the art would be able to select pellets and compounds that are suitable for the specifications of the case for the semiconductor device.
[0038] In case 16, which is a molded body, the inorganic filler is generally uniformly dispersed in a matrix mainly composed of PPS resin. Immediately after molding, the inorganic filler is covered in the PPS matrix on the surface of the case, and usually the inorganic filler is hardly exposed on the surface.
[0039] In the case 16 according to the present invention, the inorganic filler is exposed at least on the sealing material-opposing surface F. The inorganic filler being exposed means that the inorganic filler is present in a state where the surface is not covered with PPS. The exposure of the inorganic filler can be confirmed, for example, by an optical digital microscope. This is because the reflectance of the matrix and the inorganic filler are different. In this specification, the "exposed area ratio" is used for the purpose of quantifying the degree of exposure of the inorganic filler on the sealing material-opposing surface F. The exposed area ratio refers to the white area ratio (%) obtained by binarization under certain conditions per digital microscope observation field. More specifically, the white area ratio is obtained by binarizing an image of an evaluation area of 500 μm×500 μm obtained by observing the sealing material-opposing surface F of the case 16 at a magnification of 50 times using a digital microscope under conditions of brightness adjustment of 0.0 (darkest value) to 1.0 (brightest value) and a threshold value of 0.5 for black and white two-tone. When binarized under these conditions, PPS is displayed in black and the inorganic filler in white, and the proportion of each can be calculated when the sealing material-opposing surface F is evaluated on a two-dimensional plane. The exposed area ratio of a certain case 16 depends on the total area of the sealing material-opposing surface F of the case 16, but can be the average value of measurement results at multiple locations on a case where the most stress is applied. The location where the most stress is applied depends on the shape of the case, but may be, for example, an end in the longitudinal direction when the case is viewed in plan. Moreover, the multiple locations may be, for example, 5 to 10 locations.
[0040] If the exposed area ratio is greater than 0%, the adhesion to the sealing material can be improved compared to a case with an exposed area ratio of 0%. In particular, the exposed area ratio is preferably 10 to 60%, and more preferably 20 to 50%. When the exposed area ratio is in the range of 10 to 60%, the adhesion strength between the case and the sealing material can be at least twice as high as when the exposed area ratio is 0%, and when the exposed area ratio is in the range of 20 to 50%, the adhesion strength between the case and the sealing material can be at least four times as high as when the exposed area ratio is 0%.
[0041] The sealing material-facing surface F on which the inorganic filler is exposed is preferably a surface formed by, for example, a chemical treatment, and is particularly preferably an etched surface. Specific etching conditions will be described in detail in the manufacturing method of a semiconductor device, but wet etching (chemical etching) is preferable. A chemically treated surface may be preferable in that there is no risk of mechanical force being applied in the processing stage compared to a surface that has been physically treated, such as blasting, and therefore the inorganic filler can be effectively exposed without reducing the brittleness of PPS. In addition, etching may be preferable because the matrix around the inorganic filler particles is recessed and the inorganic filler particles protrude, improving adhesion to the sealing material.
[0042] A silane coupling agent layer may be optionally formed on the sealing material-facing surface F of the case 16. The silane coupling agent is interposed between the exposed inorganic filler and the sealing material 20, and can form a covalent bond with both, thereby further increasing the adhesion between the case 16 and the sealing material 20. As the silane coupling agent, it is preferable to use a silane coupling agent having an epoxy group, an amino group, or both. Specific preferred silane coupling agents include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and the like, but are not limited thereto.
[0043] The thickness of the silane coupling agent layer after drying can be, for example, 1 μm or more and 50 μm or less, and preferably 1 μm or more and 20 μm or less. After the silane coupling agent layer is formed, the exposed inorganic filler and PPS are covered with the silane coupling agent layer on the sealing material facing surface F of the case 16, and in the state in which the semiconductor device is manufactured, the silane coupling agent layer mainly contacts the sealing material 20. The silane coupling agent forms a chemical bond with both the inorganic filler and the sealing material 20, thereby preventing peeling between the case 16 and the sealing material 20. However, there may be cases in which the inorganic filler is partially exposed from the silane coupling agent layer and contacts the inorganic filler and the sealing material 20. Even in this case, the adhesion between the case 16 and the sealing material 20 can be improved compared to the case in which the sealing material 20 contacts only the PPS.
[0044] The inorganic filler may or may not be exposed from the PPS matrix on the surfaces of case 16 other than surface F facing the sealant. A person skilled in the art can appropriately select this from the viewpoint of convenience in the manufacturing method of the semiconductor device described later.
[0045] The sealing material 20 may be a cured thermosetting resin obtained by curing a thermosetting resin composition that contains a thermosetting resin base and an inorganic filler, and may optionally contain a curing agent, a curing accelerator, and additives.
[0046] The thermosetting resin base is not particularly limited, and examples thereof include epoxy resin, phenol resin, maleimide resin, cyanate resin, oxazine resin, etc. Among them, epoxy resin having at least two epoxy groups in one molecule is particularly preferred because of its high dimensional stability, water resistance, chemical resistance, and electrical insulation. Specifically, it is preferred to use aliphatic epoxy resin, alicyclic epoxy resin, or a mixture thereof. As the sealing resin, a thermosetting resin is preferred because it requires heat resistance and high insulation, and epoxy resin is particularly preferred because of its high elasticity.
[0047] Aliphatic epoxy resin refers to an epoxy compound in which the carbon to which the epoxy group is directly bonded is a carbon that constitutes an aliphatic hydrocarbon. Therefore, even if the main skeleton contains an aromatic ring, if the above condition is met, it is classified as an aliphatic epoxy resin. Examples of aliphatic epoxy resins include, but are not limited to, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD type epoxy resins, biphenyl type epoxy resins, naphthalene type epoxy resins, cresol novolac type epoxy resins, and polyfunctional epoxy resins having three or more functional groups. These can be used alone or in combination of two or more types. In addition, naphthalene type epoxy resins and polyfunctional epoxy resins having three or more functional groups have a high glass transition temperature, and are therefore also referred to as high heat resistant epoxy resins. By including these high heat resistant epoxy resins, heat resistance can be improved.
[0048] The term "alicyclic epoxy resin" refers to an epoxy compound in which two carbon atoms constituting an epoxy group constitute an alicyclic compound. Examples of alicyclic epoxy resins include, but are not limited to, monofunctional epoxy resins, bifunctional epoxy resins, and trifunctional or higher polyfunctional epoxy resins. The alicyclic epoxy resin can be used alone or in combination with two or more different alicyclic epoxy resins. When an alicyclic epoxy resin is mixed with an acid anhydride curing agent and cured, the glass transition temperature increases, so that mixing an alicyclic epoxy resin with an aliphatic epoxy resin can improve heat resistance.
[0049] The thermosetting resin base material used in the sealing material 20 may be a mixture of the above-mentioned aliphatic epoxy resin and alicyclic epoxy resin. The mixing ratio when mixing may be any, and the mass ratio of the aliphatic epoxy resin to the alicyclic epoxy resin may be about 2:8 to 8:2, or may be about 3:7 to 7:3, and is not limited to a specific mass ratio. In a preferred embodiment, the thermosetting resin base material used in the sealing material 20 is a mixture of a bisphenol A type epoxy resin and an alicyclic epoxy resin in a mass ratio of 1:1 to 1:4.
[0050] The inorganic filler may be a metal oxide or a metal nitride, and examples thereof include, but are not limited to, fused silica, silica (silicon oxide), alumina, aluminum hydroxide, titania, zirconia, aluminum nitride, talc, clay, mica, and glass fiber. These inorganic fillers can increase the thermal conductivity of the sealing material 20 and reduce the thermal expansion coefficient. These inorganic fillers may be used alone or in combination of two or more. The inorganic filler may be a microfiller or a nanofiller, and two or more inorganic fillers having different particle sizes and / or types may be mixed and used. In particular, it is preferable to use an inorganic filler having an average particle size of about 0.2 to 20 μm. The amount of inorganic filler added to the sealing material 20 is preferably 100 to 600 parts by mass, and more preferably 200 to 400 parts by mass, when the total mass of the thermosetting resin base agent and the curing agent that may be optionally contained is 100 parts by mass. If the blending amount of the inorganic filler is less than 100 parts by mass, the thermal expansion coefficient of the sealing material 20 becomes high, and peeling or cracking may occur easily. If the blending amount is more than 600 parts by mass, the viscosity of the composition increases, and extrusion moldability may deteriorate.
[0051] The thermosetting resin composition constituting the sealing material 20 may contain a curing agent as an optional component. The curing agent is not particularly limited as long as it reacts with the thermosetting resin base, preferably the epoxy resin base, and can be cured, but it is preferable to use an acid anhydride-based curing agent. Examples of the acid anhydride-based curing agent include aromatic acid anhydrides, specifically phthalic anhydride, pyromellitic anhydride, trimellitic anhydride, etc. Alternatively, examples of the acid anhydride include cyclic aliphatic acid anhydrides, specifically tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, etc., or aliphatic acid anhydrides, specifically succinic anhydride, polyadipic anhydride, polysebacic anhydride, polyazelaic anhydride, etc. The amount of the curing agent is preferably 50 parts by mass or more and 170 parts by mass or less, and more preferably 80 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the thermosetting resin (epoxy resin) base. If the amount of the curing agent is less than 50 parts by mass, the glass transition temperature may decrease due to insufficient crosslinking, and if it is more than 170 parts by mass, it may be accompanied by a decrease in moisture resistance, high heat distortion temperature, and heat resistance stability. In addition, when a bisphenol A type epoxy resin is used alone or a mixture of a bisphenol A type epoxy resin and a high heat resistant epoxy resin exemplified above is used as the thermosetting resin base, it may be preferable not to use a curing agent because heat resistance is improved. The compounding ratio of the high heat resistant epoxy resin may be, for example, 10% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 25% by mass or less, when the total mass of the thermosetting resin base is 100%. This range is preferable because heat resistance is improved and viscosity does not increase.
[0052] A curing accelerator may be added as an optional component to the thermosetting resin composition constituting the sealing material 20. As the curing accelerator, imidazole or its derivatives, tertiary amines, boric acid esters, Lewis acids, organometallic compounds, organic acid metal salts, etc. may be appropriately blended. The amount of the curing accelerator added is preferably 0.01 parts by mass or more and 50 parts by mass or less, more preferably 0.1 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the thermosetting resin base.
[0053] The thermosetting resin composition constituting the encapsulant 20 may also contain optional additives to the extent that the properties of the composition are not impaired. Examples of additives include, but are not limited to, flame retardants, pigments for coloring the resin, and plasticizers and silicone elastomers for improving crack resistance. These optional components and the amounts of them to be added can be appropriately determined by those skilled in the art according to the specifications required for the semiconductor device and / or the encapsulant.
[0054] The sealing material 20 may be a single layer made of one type of resin having the composition exemplified above, or may be a layer including two or more layers. A layer of a thermoplastic resin or silicone rubber may be further provided on one or more thermosetting resin layers.
[0055] In the semiconductor device according to this embodiment, the inorganic filler is exposed from the PPS matrix on the sealing material-opposing surface F of the case. Therefore, it is possible to increase the adhesion between the case and the resin constituting the sealing material, and to prevent the intrusion of moisture and gas. Furthermore, it is possible to prevent local stress concentration due to partial peeling between the case and the sealing material. In the conventional case, the surface is covered with PPS, and the inorganic filler is present inside, so that it has almost no polarity, and it has only been known that the surface area can be increased by roughening or the like. Although it is not intended to be bound by theory, according to the present invention, by exposing the inorganic filler having a polar group from the PPS matrix, it is possible to impart polarity to the case surface and improve the adhesion to the sealing material.
[0056] For the purpose of explaining the present invention, the cross-sectional structure of a specific module is shown in FIG. 1, but the configuration of the laminated substrate, semiconductor element, conductive connection member, and external terminal is not limited to the illustrated form. It is sufficient that the relationship between the sealing material and the case surface satisfies the above. For example, the conductive connection member may be only one of a lead frame, a wire, and an implant pin, or may include two or more of these. In addition, for example, a printed circuit board connected to the front surface electrode of the semiconductor element by an implant pin may be further included, and the printed circuit board may be insulated and sealed. In addition, for example, a primer layer may be provided on the surface of a member that contacts the sealing material, such as a semiconductor element, a laminated substrate, and a conductive connection member.
[0057] Next, a semiconductor device according to an embodiment of the present invention will be described from the viewpoint of a manufacturing method thereof. The manufacturing method of the semiconductor device includes the following steps. (1) A process for producing a case containing an inorganic filler in a matrix containing polyphenylene sulfide (2) A step of immersing the case in an etching solution to expose the inorganic filler from the matrix. (3) A step of placing a semiconductor element mounted on a laminated substrate in the case obtained by the exposing step. (4) A process of filling the case in which the semiconductor element is disposed with a sealant to seal the case. Optionally, after step (2) and before step (3), a step of forming a silane coupling agent layer on the surface where the inorganic filler is exposed may be included. Each step will be described below.
[0058] (1) Case manufacturing process In the first step, a case material containing PPS and an inorganic filler is molded to produce a case containing an inorganic filler in a matrix containing polyphenylene sulfide. The case can be manufactured, for example, by manufacturing a mold that matches the specifications of the case by a normal method and performing injection molding. The composition ratio of PPS and the inorganic filler and other additives may be as described above. In addition, generally, metal members such as external terminals can be integrated with the case and injection molded. In addition to injection molding, extrusion molding, compression molding, blow molding, vacuum / pressure molding, and molding using a 3D printer are also possible.
[0059] (2) Etching process In the second step, the case obtained in the first step is immersed in an etching solution to etch the surface of the case (chemical etching). If the case obtained in the first step includes a member to be protected from the etching solution, such as when a metal member such as an external terminal is integrated into the case, the protected portion can be masked before being immersed in the etching solution. Surfaces other than the surface facing the sealing material, such as the outer surface of the case, can also be masked.
[0060] The etching solution is PPS etching rate V pps and the etching rate of inorganic filler V i But the following relationship:V pps >V i Any liquid that satisfies the above condition may be used. For example, concentrated nitric acid, 50% chromic acid, 5% hypochlorous acid, concentrated sulfuric acid, etc. may be used. Among them, it is preferable to use concentrated nitric acid as the etching solution and immerse the case in the etching solution at about 80 to 90°C for about 10 to 60 hours to perform etching. The composition, temperature, and processing time of the etching solution can be determined by obtaining the relationship between the etching conditions for a case material of a specific composition and the exposed area ratio of the inorganic filler through preliminary experiments.
[0061] After the case is immersed in the etching solution for a predetermined time, the case is washed with water, dried, and optionally the masking is removed, resulting in a case in which the inorganic filler is exposed from the PPS matrix over at least the entire surface F of the sealing material facing surface.
[0062] As an optional step after the second step, a step of forming a silane coupling agent layer on the surface of the case 16 where the inorganic filler is exposed (sealant-facing surface F) can be performed. The silane coupling agent layer can be formed by coating, spraying, or the like. In order to obtain the desired layer thickness of the silane coupling agent layer, the relationship between the concentration of the silane coupling agent solution, the spraying time, and the layer thickness after drying can be obtained through a preliminary experiment, and the coating or spraying conditions of the silane coupling agent solution can be determined. After coating, it is preferable to thoroughly dry the silane coupling agent solution for 5 to 24 hours at a temperature required according to the specifications of the silane coupling agent used.
[0063] (3) Placement and assembly process In the third step, a semiconductor device is assembled using the case obtained in the second step or, optionally, in the step of forming a silane coupling agent layer. The heat sink 13, the laminated substrate 12, and the semiconductor element 11 are bonded by a normal method. Next, the case 16 is attached and fixed to the heat sink 13 using resin or the like. Thereafter, the lead frame 18 is bonded, and wire bonding is performed with the aluminum wire 14. Depending on the configuration of the semiconductor device, an implant pin and a printed circuit board can be bonded optionally. In addition, a step of forming a primer layer on the surfaces of the members that come into contact with the sealing material in the next step, such as the semiconductor element, the laminated substrate, and the conductive connecting member, can also be performed. It is not preferable to provide a primer layer on the surface of the case.
[0064] (4) Sealing process In the fourth step, the assembled members are insulated and sealed according to a normal method. Specifically, a thermosetting resin composition constituting the sealing material 20 is injected into the case 16 and heat-cured. The heat-curing step can be, for example, a two-stage curing step. When an epoxy resin is used as the main thermosetting resin, the resin is heated at 90 to 120°C for 1 to 2 hours to be in a semi-cured state. After that, heating can be further performed at 175 to 185°C for 1 to 2 hours (main curing). However, the temperature and time are not limited to a specific temperature and time, and there are cases where two-stage curing is not necessary. Optionally, in a semiconductor device in which the sealing material is composed of two or more layers, two or more sealing layers can be appropriately formed.
[0065] According to the method for manufacturing a semiconductor device according to the present embodiment, the inorganic filler can be exposed from the matrix of the PPS constituting the case, and the inorganic filler can be configured to be in contact with the sealing material. Alternatively, the inorganic filler can be configured to be in contact with the silane coupling agent layer optionally. This makes it possible to manufacture a semiconductor device with improved adhesion between the case and the sealing material, compared to conventional semiconductor devices in which the PPS constituting the case was mainly in contact with the sealing material. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples of the present invention. However, the present invention is not limited to the scope of the following examples.
[0067] [Reference Example] Examination of conditions for exposing inorganic filler In order to manufacture a case in which the inorganic filler is exposed from a matrix containing PPS, the conditions for exposing the inorganic filler by chemical etching were examined. A resin composite substrate (10 x 10 x 1 (mm)) was manufactured consisting of a matrix containing PPS simulating a case and silica as an inorganic filler. PPS resin Torelina A610 (Toray) was used as the matrix. Substrates with a silica filling rate of 50 mass% and 70 mass% were obtained by injection molding. When the surface was observed with a digital microscope (Keyence Corporation, model number VHX-7000) before chemical etching, no exposed silica was found in either case.
[0068] These substrates were immersed in concentrated nitric acid at 80°C for etching. The definition of the exposed area ratio of the inorganic filler is as described above. The relationship between the etching time (hr) and the exposed area ratio (%) of the inorganic filler is shown in FIG. 2. It was confirmed from FIG. 2 that the exposed area ratio could be controlled within the range of approximately 10 to 65% by controlling the etching time using concentrated nitric acid at 80°C for both substrates with an inorganic filler filling ratio of 50 mass% and substrates with an inorganic filler filling ratio of 70 mass%.
[0069] [Example] (1) Evaluation of exposed area ratio, inorganic filling ratio and adhesion strength A pudding cup test was performed to evaluate the peel strength (shear strength) between the case and the sealing material in the power semiconductor module shown in FIG. 1. A resin composite substrate of a matrix containing PPS and silica, which is an inorganic filler, was etched to expose the silica, and used as a substrate for the pudding cup test. Concentrated nitric acid at 93°C was used for etching. An epoxy resin composition usable as a sealing material was molded on this substrate to have a bottom diameter of 3.6 mm, a top diameter of 3.0 mm, and a height of 3.0 mm, and a thermal curing reaction was performed at 100 to 180°C for 3 hours to obtain a test piece of an epoxy resin cured product molded on the substrate. The specific composition of the epoxy resin composition was as follows. As the epoxy resin base material, epoxy resin ME-276 (manufactured by Pernox Co., Ltd.) was used, and 121 parts by mass of MV-138 (manufactured by Pernox Co., Ltd.) was added as an acid anhydride curing agent relative to 100 parts by mass of the epoxy resin base material. The inorganic filler used was fibrous silica (manufactured by Nippon Electric Glass Co., Ltd.) with an average particle size of 10 μm, and 270 parts by mass was added when the total mass of the base epoxy resin and hardener was 100 parts by mass.
[0070] A force gauge (load measuring device: Imada ZTA-1000N) was used to measure the shear strength. The measurement conditions were as follows: the epoxy resin cured material was pressed parallel to the adhesive surface at a speed (strain rate) of 0.2 mm / s, and the strength at which the interface between the epoxy resin cured material and the resin composite substrate peeled off and broke was taken as the adhesion strength.
[0071] The filling rate (mass%) of the inorganic filler (silica), the exposed area rate (%) of the inorganic filler, the etching time condition (hr) for exposing the inorganic filler, and the adhesion strength (MPa) in Examples 1 to 9 and Comparative Example 1 are shown in Table 1. The relationship between the exposed area rate (%) and the adhesion strength (MPa) is shown in FIG.
[0072] [Table 1]
[0073] In all of Examples 1 to 9, the adhesive strength between the case and the sealing material was improved compared to the comparative example in which the exposed area ratio of the inorganic filler was 0%. The adhesive strength between the case and the sealing material may be about 15 MPa, preferably 20 MPa or more, and more preferably 35 MPa or more. From this, it can be said that the exposed area ratio of the inorganic filler that can improve the adhesive strength between the case and the sealing material is about 10 to 60%, preferably 12 to 60%, and particularly preferably 20 to 50%.
[0074] (2) Evaluation of silane coupling agent layer and adhesion strength Next, a silane coupling agent layer was formed on the surface of a case with a filling rate of 50% by mass of inorganic filler (silica) and an exposed area rate of 50%, and the adhesion strength was evaluated. A silane coupling agent manufactured by Shin-Etsu Chemical Co., Ltd. was used, and water was added to dilute it 2 to 5 times, and then it was stirred until it became uniform. Next, the diluted and stirred silane coupling agent was sprayed onto the exposed surface of the inorganic filler, and dried at 120°C for 24 hours. The adhesion strength was measured by changing the type of silane coupling agent and the layer thickness. The epoxy resin composition used in the adhesion strength measurement and the measurement conditions for adhesion strength were the same as those in (1) above. The difference in adhesion strength depending on the type of silane coupling agent is shown in Table 2. In any case where a silane coupling agent was used, the layer thickness after drying was set to 5 μm. In addition, the difference in adhesion strength depending on the layer thickness when the silane coupling agent was epoxy KBM-403 is shown in Table 3. In both Tables 2 and 3, the exposed area rate indicates the exposed area rate of the inorganic filler before the silane coupling agent is applied.
[0075] [Table 2]
[0076] [Table 3]
[0077] When an amino group-containing silane coupling agent and an epoxy group-containing silane coupling agent were used as the silane coupling agent, an improvement in adhesion strength was observed, and when the layer thickness was 1 to 20 μm, the improvement in adhesion strength was large.
[0078] (3) Exposure method and adhesion strength evaluation The adhesiveness between the epoxy resin and a substrate simulating a PPS case filled with 50% by mass of silica using the same material as in (1) was examined for the cases of using chemical etching and blasting as a method for exposing the inorganic filler. In Example Z1 using chemical etching, the inorganic filler was exposed by heating the substrate in concentrated nitric acid at 80°C for 30 hours. On the other hand, in Example Z2 using blasting, air blasting was performed on one side of the substrate. The air blasting device used was a gravity type SGK-4LD-401 with a nozzle diameter of Φ9 mm, a processing pressure of 0.5 MPa, and a polishing agent Polyextra (low hardness) with a Mohs hardness of 3. In both methods, the treatment was performed with the aim of achieving an exposed area ratio of 30%. The epoxy resin composition used to measure the adhesive strength and the measurement conditions for the adhesive strength were the same as in (1) above.
[0079] In Example Z1, where chemical etching was used, when the exposed area ratio reached 30%, the inorganic filler silica was exposed from the matrix containing PPS, and the adhesion strength was 40 MPa. In Example Z2, where blasting was used, the exposed area ratio reached 30%, and the adhesion strength was about 20 MPa, achieving the required adhesion strength. When blasting was used, there were some areas where the silica was not completely exposed, whereas when chemical etching was used, the batch process allowed for more uniform roughening, demonstrating that a higher adhesion strength could be achieved.
[0080] From the above, it was confirmed that in both methods, chemical etching and blasting, the adhesion strength is improved by exposing the inorganic filler from the matrix, and from the viewpoint of the extent of improvement, chemical etching is more advantageous and more preferable. [Explanation of symbols]
[0081] 11 semiconductor element, 12 laminated substrate, 121 first conductive plate, 122 insulating substrate 123a, 123b second conductive plate, 13 heat sink, 14 aluminum wire, 15 external terminal, 16 case, 17 bonding layer, 18 lead frame 20 sealing layer, F sealing material facing surface
Claims
1. a case containing an inorganic filler in a matrix containing polyphenylene sulfide; a semiconductor element mounted on a laminated substrate; a sealing material for sealing the semiconductor element; A semiconductor device comprising: The semiconductor device, wherein the inorganic filler is exposed from the matrix on a surface of the case facing the sealing material.
2. 2. The semiconductor device according to claim 1, wherein a content of said inorganic filler relative to a total mass of said case is 40 to 70 mass %, and an exposed area ratio of said inorganic filler is 10 to 60%.
3. 2. The semiconductor device according to claim 1, wherein said inorganic filler is a fibrous inorganic filler.
4. The semiconductor device according to claim 1 , wherein the inorganic filler is selected from a metal oxide or a metal nitride.
5. 2. The semiconductor device according to claim 1, wherein the sealing material includes a thermosetting resin selected from the group consisting of epoxy resin, maleimide resin, cyanate resin, and oxazine resin.
6. 2. The semiconductor device according to claim 1, wherein the surface of said case facing said sealing material is an etched surface.
7. The semiconductor device according to claim 1 , wherein the exposed inorganic filler is in contact with the encapsulant.
8. 2. The semiconductor device according to claim 1, wherein a silane coupling agent layer is formed on a surface of said case facing said sealing material.
9. The semiconductor device according to claim 8 , wherein the silane coupling agent layer is in contact with the sealing material.
10. producing a case comprising an inorganic filler in a matrix comprising polyphenylene sulfide; immersing the case in an etching solution to expose the inorganic filler from the matrix; a step of placing a semiconductor element mounted on a laminated substrate in the case obtained by the exposing step; a step of filling a sealing material into the case in which the semiconductor element is placed, and sealing the case; A method for manufacturing a semiconductor device, comprising:
11. The method according to claim 10 , further comprising the step of forming a silane coupling agent layer on the surface where the inorganic filler is exposed, before the step of placing the semiconductor element.
12. The method according to claim 11, wherein the silane coupling agent is a silane coupling agent containing an epoxy group or an amino group.